Keterampilan Abad 21 dalam Modul Ajar Bahasa Indonesia Kurikulum Merdeka di Sekolah Menengah Kejuruan - Sandi Irawan; Muhammad Mukhlis (Universitas Mulawarman, 2023)
This study aims to describe 21st-century skills in Indonesian language teaching modules for class X semester I of the independent curriculum created by educators at SMK Negeri 3 Pekanbaru. It is important because educators must develop independent curriculum teaching modules that integrate with 21st-century skills to prepare students to face the 21st-century era through a learning process that has been designed. This study used a qualitative approach with content analysis methods. Content analysis was conducted to find data on 21st-century skills in the Indonesian language teaching module document for the independence curriculum. Data collection techniques using documentation. The research data is in the form of learning activities and practice questions in the Indonesian language teaching module document, the independent curriculum. Data were analyzed using content analysis techniques consisting of three stages: data reduction, data presentation, and drawing conclusions. The results obtained in this research are century skill consisting of critical thinking skill found 45 times at 35.1%, communication found 63 at 49.2%, collaboration found 13 at 10.1%, creative and innovative found 7 at 5.4%, which is included in the Indonesian language teaching module class X independent curriculum at SMK Negeri 3 Pekanbaru.